1997
DOI: 10.1016/s0886-3350(97)80280-5
|View full text |Cite
|
Sign up to set email alerts
|

Mesopic vision in myopia corrected by photorefractive keratectomy, soft contact lenses, and spectacles

Abstract: Myopic PRK may lead to long-term impairment of mesopic vision, while soft contact lens use does not seem to markedly influence mesopic vision in eyes with low to moderate myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 21 publications
2
11
0
2
Order By: Relevance
“…Moreover, though in the present paper we do not directly measure the response of myopic and hyperopic subjects wearing either contact or ophthalmic lenses, our results are similar to those of Schlote et al [7] and Jewelewicz et al [8] who did not find important differences in night vision for ammetropic subjects wearing either of the two refractive corrections. Thus, our preliminary results suggest that our methodology of inducing ammetropies in emmetropes could be a reliable way of studying, in a controlled manner, the effects of glare on subjects wearing refractive corrections.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, though in the present paper we do not directly measure the response of myopic and hyperopic subjects wearing either contact or ophthalmic lenses, our results are similar to those of Schlote et al [7] and Jewelewicz et al [8] who did not find important differences in night vision for ammetropic subjects wearing either of the two refractive corrections. Thus, our preliminary results suggest that our methodology of inducing ammetropies in emmetropes could be a reliable way of studying, in a controlled manner, the effects of glare on subjects wearing refractive corrections.…”
Section: Discussionsupporting
confidence: 87%
“…Some researchers have evaluated the influence of the different types of corrections under night vision conditions. For example, Schlote et al [7] measured contrast vision and glare sensitivity under mesopic conditions in myopic eyes corrected by soft contact lenses and spectacles and found that their use does not seem to markedly influence mesopic vision in eyes with low to moderate myopia. Moreover Jewelewicz et al [8] evaluated night vision disturbances for myopic subjects finding that there was no significant difference in image degradation between subjects wearing spectacles and soft contact lenses.…”
Section: Introductionmentioning
confidence: 99%
“…This device is used as a clinical screening test for mesopic vision under conditions of low contrast and glare. Currently it is recommended by the German Ophthalmological Society as a primary night vision screener to test drivers for private and/or commercial vehicle licenses (14,32). The Mesotest II b has great utility as a standardized instrument for night vision research studies because it provides a quantifiable performance measure of night/mesopic visual function both with and without glare.…”
Section: Mesopic Low Contrast Vision Testingmentioning
confidence: 99%
“…Post-PRK QoV issues, especially problems that could degrade I vision at night (25-3 1), must be thoroughly evaluated in terms of potential mission impact. Critically important to night missions are any potential effects on mesopic low contrast visual acuity (VA), both with and without glare (32)(33)(34)(35), and performance with night vision devices, especially Night Vision Goggles. Night Vision Goggle (NVG) visual acuity in aviators has been previously described and well documented (36)(37)(38)(39)(40)(41)(42), but little is known regarding NVG visual acuity performance after PRK.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudos evidenciam alteração da qualidade visual com decréscimo da sensibilidade ao contraste no pós-operatório (3)(4) . Em fase do avanço no campo da análise de frente de onda, já está bem estabelecido que as principais causas associadas aos distúrbios de visão noturna estão relacionadas ao aumento das aberrações oculares monocromáticas e ao fenômeno da dispersão da luz através da córnea operada (5)(6) .…”
Section: Resumo Introduçãounclassified